(untitled) (Advances in Applied Mathematics and Mechanics, 2013)
This paper presents a physical investigation and mathematical analysis on mechanical behavior of the regular jugged discontinuity. In particular, we focus on the creep property of structural plane with various slope angles under different normal stress through shear creep tests of structural plane under shear stresses. According to the test results, the shear creep property of structural plane was described and the creep velocity and long-term strength of the structural plane during shear creep were also investigated. An empirical formula is finally established to evaluate shear strength of discontinuity and a modified Burger model was proposed to represent the shear deformation property during creep.